DESIGN OF MOOC+SPOC PLATFORM ON RESEARCH IN VOCATIONAL EDUCATION - Tri Budi Utami, Atikah; Yahya, Muhammad; Purnamawati, Purnamawati (Pascasarjana Universitas Negeri Makassar, 2025)
The integration of online platforms has changed and significantly transformed the educational landscape, particularly in technical fields like process control systems. ATRIBUT, our innovative platform, is at the forefront of this transformation. It seamlessly blends MOOCs' scalability with SPOCs' personalized attention, combining asynchronous and synchronous learning methods. This approach fosters a more engaging environment and opens up new possibilities for students, educators, and the process control system education field. ATRIBUT is not just a theoretical concept but a practical solution designed explicitly for process control systems. It covers critical areas such as automation, control theory, and system dynamics, ensuring students gain theoretical and practical knowledge. The platform's adaptive learning technologies and data analytics further enhance its practicality, personalizing content, tracking student progress, and optimizing learning outcomes, providing a comprehensive and practical learning experience. A core feature of ATRIBUT is its emphasis on collaboration. Group projects, peer reviews, and interactive tools facilitate a sense of community among learners. The cloud-based infrastructure supports scalability and accessibility, ensuring an inclusive and user-friendly experience where every learner is considered and valued. This research evaluates the effectiveness of ATRIBUT through an experimental design, comparing two groups of students: one using ATRIBUT and another following traditional learning methods. Data collected from pre-tests, post-tests, and questionnaires will measure learning outcomes, engagement, and satisfaction. Statistical analysis will determine if ATRIBUT significantly enhances learning and motivation compared to traditional approaches, aiming to provide evidence of its potential in process control system education.